Analisis Diskriminan Untuk Mengevaluasi Kondisi Fisik Atlet Hockey Surabaya - Mohammad Faruk, (Kepelatihan Olahraga, 2011)
The development of discriminant analysis model aims to evaluate the physical condition of hockey athletes. Discriminant analysis model is applied later in Delphi Programming Language to facilitate the physical condition evaluation of Surabayas hockey athletes. In order to get a model of discriminant analysis which can be changed into a mathematical function to distinguish the physical condition of athletes who are good and less, thedata processing of physical condition evaluation of Surabayas hockey athletes is perfomed with the aid of computer programs statistic. In this research, there are two categories in selecting, the Non-Hockey and Hockey. The result of Discriminant analysis can classify the ability of the group until 97.8%, in other word it means that it can be used to classify the physical condition of athletes hockey Surabaya.